(untitled) (World Economics and Finance Bulletin, 2023)
The main objective of this research is to verify the inflation rate and its impact on the GDP growth rate for the period 2010-2020, on an annual basis. In order to verify the relationship of inflation as an independent variable with the growth rate of GDP. Thus, Diagnostic tests were employed to examine the model’s data, such as the Durbin-Watson test for serial correlation analysis. For the tests, solid outcomes and indicators were achieved., and the standard economic results indicate that the rate of inflation has a positive impact on the rate of growth of the GDP in Iraq.